A Review of the Forest Service's National Visitor Use Monitoring (NVUM) Program. (April 2020) - English, Donald B.K.; White, Eric M.; Bowker, J.M.; Winter, Susan A.
Abstract : The National Visitor Use Monitoring (NVUM) program data underlies estimates of the volume of recreation use of the National Forest System. The data also enable estimation of both the local economic contributions and nonmarket benefits of that visitation. Applications include evaluating the effects of natural disasters, site characteristics, and climate change, as well as expenditure and benefit transfers. This article describes the history and science background of the NVUM program, outlines the methods used in estimating market and nonmarket economic outcomes, and lists some examples of results found in the literature.